AKUMULASI MODAL DALAM PRODUKSI PROGRAM TELEVISI - Mohammad Yozar Putranto; Mulharnetti Syas (Jurusan Ilmu Komunikasi Universitas Andalas, 2022)
Media in the process of producing and delivering information in the form of broadcasting programs to targeted consumers. The facts show that media has grown not only as a social, political and cultural tool but also as a company that emphasizes economic benefits. The production process of broadcast or television involves several elements such as labor, equipment, time and other related resources that require large capital. While the Media as an institution that lives in the public sphere with challenges to realize public space in society. The research method used is a Case Study where researchers collect data, take meaning, and gain understanding from interviews with some of the staff involved. The results showed that the management of Elshinta TV was able to carry out its function as a business institution, as evidenced by the achievement of surplus value which evidenced by the bigger advertising sales revenue than the production costs of the program. But it has not been able to ideally realize the public sphere in the midst of modern society. The suggestion of this research is to encourage TV stations not only to gain profit, but also to seriously answer the challenges of realizing public space in society.